Pertanggungjawaban Terhadap Pelanggaran Penggunaan Bom Cluster Menurut Hukum Humaniter Internasional - Hidayat, Rahmat Safril; Anwar, Arman; Waas, Richard Marsilio (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Cluster bombs have quite a dangerous effect on civilians and can take lives because when these bombs are launched into the target area they usually do not explode simultaneously, even the explosions can occur at a later date or even when the war is over.Purposes of the Research: This writing aims to examine and find out the forms of violations of the law on the use of cluster bombs in war according to humanitarian law, to study and find out about the accountability for the use of cluster bombs assigned to perpetrators and as one of the requirements for completing studies at the Faculty of Law, Pattimura University.Methods of the Research: The Juridical-Normative research method with the type of doctrinal research is also known as library research or document study because this research is carried out or shown only on written regulations or other legal materials.Results of the Research: The results of the study show that the prohibition of the use of cluster bombs according to International Humanitarian Law has been regulated in the 2008 Convention On Cluster Munitions (CCM), namely each country promises to clean up and destroy, or ensure the cleaning and destruction of, the remains of cluster ammunition located in cluster munitions. Contamination under its jurisdiction or control. And the form of responsibility for the perpetrators is the responsibility of the state, namely the state that violates international agreements. As well as sanctions that can be given for the use of cluster bombs that are given by the United Nations in the form of reducing the degree of diplomatic relations or attacks using armed power by the UN security council, sanctions can also be given based on humanitarian law in particular Additional Protocol I of 1977 and International Humanitarian Law customs in relation to state responsibility in international law, which can be in the form of compensation, in the form of satisfaction given through acknowledgment of actions, expressions of remorse and official apologies by the state relating to the International Criminal Court.